Descentralización y regionalización Necesidad de su realización - Vegas Pozo, José (2006)
In this text I meditate on some structural problems of contemporary Peruvian society, specifically about the economic, political and administrative decentralization and the process of the constitution of regions where the people should participate democratically. In this way regional identity will be real.